Wojna hybrydowa jako nowe zjawisko w sztuce wojennej XXI wieku - Renn, Przemysław (Refleksje. Pismo naukowe studentów i doktorantów WNPiD UAM, 2018)
This article provides an insight into a new type of war - a hybrid war, which manifest itself through actions of Russia on the area of Eastern Ukraine. The author makes an attempt to classify hybrid war among other armed conflicts defined in the study of international security and relations, simultaneously trying to determine characteristic features of this phenomenon. The author hypothesize that deeper research into the problem may result in the necessity of creating new evaluative framework other than the one used for the conventional conflicts.